2008
DOI: 10.1007/s00280-008-0845-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mRNA by Q-RTPCR and protein expression by AQUA of the M2 subunit of ribonucleotide reductase (RRM2) in human tumors

Abstract: Purpose-The purpose of this study was to evaluate baseline RRM2 protein and gene expression in tumors of patients receiving 3-AP.Experimental Design-Tumor blocks from patients enrolled in phase I and II clinical studies using 3-AP, were evaluated for RRM2 gene and protein expression by quantitative real time polymerase chain reaction (Q-RTPCR) and automated quantitative analysis, (AQUA).Results-Esophageal and gastric cancers overexpressed RRM2 protein when compared to prostate cancer (Z-score, 0.68 ± 0.94 SD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…RRM2 is known to function as a tumor driver during carcinogenesis and high expressed in esophageal cancer, gastric cancer, colon cancer, and hepatocellular cancer [21][22][23][24][25]. This study also showed that RRM2 was higher expressed in most PTC samples and seemed to be more intensively stained in UTC tissues.…”
Section: Discussionsupporting
confidence: 57%
“…RRM2 is known to function as a tumor driver during carcinogenesis and high expressed in esophageal cancer, gastric cancer, colon cancer, and hepatocellular cancer [21][22][23][24][25]. This study also showed that RRM2 was higher expressed in most PTC samples and seemed to be more intensively stained in UTC tissues.…”
Section: Discussionsupporting
confidence: 57%
“…1). There have been few studies that have examined RRM2 protein expression in human cancer tissues [18][19][20]. Kolesar expression in only four cases of "esophageal and gastric cancers" and found that those cancers overexpressed RRM2 protein when compared with prostate cancer [19].…”
Section: Discussionmentioning
confidence: 98%
“…This method has now been well established and is used by many laboratories [24-32]. Measurements can be conducted on whole specimens or TMAs.…”
Section: Discussionmentioning
confidence: 99%